1991
DOI: 10.14430/arctic1539
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption Patterns and Use of Country Foods by Native Canadians Near Wood Buffalo National Park, Canada

Abstract: ABSTRACT. This study examined food consumption patterns of native (Indian and Metis) Canadians living in a boreal forest area with good access to both store-bought and country foods (traditional foods from the land, such as wild animals, birds, fish and berries). Frequency of use by season of 48 country foods by 120 households was examined by interview with the female household head. Wenty-four-hour recalls of individual food consumption on four separate days over two seasons were obtained by interview with 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
2
16
1
Order By: Relevance
“…These results support the general opinion that men more than women experience a need to eat traditional food. A more frequent consumption of traditional food by men has also been described among native Canadians (Wein et al, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…These results support the general opinion that men more than women experience a need to eat traditional food. A more frequent consumption of traditional food by men has also been described among native Canadians (Wein et al, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…Traditional food systems are also highly influenced by resource availability and the physical environment (Kuhnlein et al, 2001;Waldram, 1985;Wein, Henderson Sabry, & Evers, 1991). Previous studies examining traditional food access and availability have often taken place in remote regions where environmental safety issues associated with traditional foods such as wild meats and fish have been viewed with concern, particularly in northern communities where contaminants have accumulated up the food chain in many species (Furgal & Seguin, 2006;Kuhnlein & Chan, 2000;Receveur et al, 1997;Tsuji et al, 2005;Waldram, 1985;Wein et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional food systems are also highly influenced by resource availability and the physical environment (Kuhnlein et al, 2001;Waldram, 1985;Wein, Henderson Sabry, & Evers, 1991). Previous studies examining traditional food access and availability have often taken place in remote regions where environmental safety issues associated with traditional foods such as wild meats and fish have been viewed with concern, particularly in northern communities where contaminants have accumulated up the food chain in many species (Furgal & Seguin, 2006;Kuhnlein & Chan, 2000;Receveur et al, 1997;Tsuji et al, 2005;Waldram, 1985;Wein et al, 1991). Comparatively, in southern Canada, few studies have reported on environmentally contaminated locally harvested foods (Abonyi, 2001;Bruyere & Garro, 2000;Chan, Trifonopoulos, Ing, Receveur, & Johnson, 1999;Garro, 1994;Lang, 1989), or their decreased access due to environmental modification, such as urban development and the displacement of Indigenous species (Doolan, 1991;Hlimi, Skinner, Hanning, Martin, & Tsuji, 2012;O'Neil, Reading, & Leader, 1998;Turner & Turner, 2008;Wheatley & Paradis, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Frequency of traditional food use has been found to be higher among males and increase with age in both genders Receveur et al, 1997;Wein et al, 1991), although clear trends have not been found when evaluating age and gender together.…”
Section: Frequency Of Food Usementioning
confidence: 93%
“…In Yukon First Nations, terrestrial animals make up the largest group of traditional foods, with moose and caribou the most frequently consumed species (Batal et al, 2005;Nakano et al, 2005b;Wein & Freeman, 1995). Men generally consume more traditional foods than women, and older individuals tend to consume more traditional foods than younger individuals; however there is not a clear pattern when age and gender are considered together Receveur et al, 1997;Wein et al, 1991). In a study of 44 Dene/Metis, Yukon First Nations and Inuit communities, men aged 20-40 consumed more traditional food than women of the same age group .…”
Section: Food Use and Nutritionmentioning
confidence: 99%